Outcome and prognostic factors in patients with brain metastases from small-cell lung cancer treated with whole brain radiotherapy - Bernhardt, Denise; Adeberg, Sebastian; Bozorgmehr, Farastuk; Opfermann, Nils; Hörner-Rieber, Juliane; König, Laila; Kappes, Jutta; Thomas, Michael; Herth, Felix; Heußel, Claus Peter; Warth, Arne; Debus, Jürgen; et al. (Journal of neuro-oncology, 2017)
The purpose of this study was to evaluate prognostic factors associated with overall survival (OS) and neurological progression free survival (nPFS) in small-cell lung cancer (SCLC) patients with brain metastases who received whole-brain radiotherapy (WBRT). From 2003 to 2015, 229 SCLC patients diagnosed with brain metastases who received WBRT were analyzed retrospectively. In this cohort 219 patients (95%) received a total photon dose of 30 Gy in 10 fractions. The prognostic factors evaluated for OS and nPFS were: age, Karnofsky Performance Status (KPS), number of brain metastases, synchronous versus metachronous disease, initial response to chemotherapy, the Radiation Therapy Oncology Group recursive partitioning analysis (RPA) class and thoracic radiation. Median OS after WBRT was 6 months and the median nPFS after WBRT was 11 months. Patients with synchronous cerebral metastases had a significantly better median OS with 8 months compared to patients with metachronous metastases with a median survival of 3 months (p < 0.0001; HR 0.46; 95% CI 0.31-0.67). Based on RPA classification median survival after WBRT was 17 months in RPA class I, 7 months in class II and 3 months in class III (p < 0.0001). Karnofsky performance status scale (KPS < 70%) was significantly associated with OS in both univariate (HR 2.84; p < 0.001) and multivariate analyses (HR 2.56; p = 0.011). Further, metachronous brain metastases (HR 1.8; p < 0.001), initial response to first-line chemotherapy (HR 0.51, p < 0.001) and RPA class III (HR 2.74; p < 0.001) were significantly associated with OS in univariate analysis. In multivariate analysis metachronous disease (HR 1.89; p < 0.001) and initial response to chemotherapy (HR 0.61; p < 0.001) were further identified as significant prognostic factors. NPFS was negatively significantly influenced by poor KPS (HR 2.56; p = 0.011), higher number of brain metastases (HR 1.97; p = 0.02), and higher RPA class (HR 2.26; p = 0.03) in univariate analysis. In this series, the main prognostic factors associated with OS were performance status, time of appearance of intracranial disease (synchronous vs. metachronous), initial response to chemotherapy and higher RPA class. NPFS was negatively influenced by poor KPS, multiplicity of brain metastases, and higher RPA class in univariate analysis. For patients with low performance status, metachronous disease or RPA class III, WBRT should be weighed against supportive therapy with steroids alone or palliative chemotherapy.